Plasmodium knowlesi infection: a diagnostic challenge. (22nd April 2013) - Fan, Lijia; Lee, Shir Ying; Koay, Evelyn; Harkensee, Christian
Abstract : Plasmodium knowlesi malaria is an uncommon, but highly prevalent parasitic infection in parts of Malaysia. This is the case of a 14-year-old Singaporean boy presenting to our emergency department with an 11-day history of fever following a school trip to Malaysia. Hepatosplenomegaly was the only clinical finding; laboratory tests showed thrombocytopaenia, lymphopaenia, mild anaemia and liver transaminitis. Specific malaria antigen tests were negative, but the peripheral blood film showed plasmodia with atypical features, with a parasite load of 0.5%. PCR confirmed the diagnosis of P knowlesi . The patient was successfully treated with chloroquine. The clinical course of P knowlesi malaria is indistinguishable from that of Plasmodium falciparum . This case highlights the importance of taking detailed travel history, careful examination of malaria blood films and judicious use of molecular techniques. Antigen tests alone may have missed a malaria diagnosis altogether, while blood film examination may wrongly identify the species as Plasmodium malariae or P falciparum . Third-generation PCR assays can be used to reliably identify P knowlesi .